Synthesis of Amphiphilic Block Copolypept(o)ides by Bifunctional Initiators: Making PeptoMicelles Redox Sensitive. Issue 23 (7th September 2015) - Holm, Regina; Klinker, Kristina; Weber, Benjamin; Barz, Matthias
Abstract : In this work, the synthesis of polypeptoid‐ block ‐polypeptide copolymers (block copolypept(o)ides) based on bifunctional initiators is described, which introduces a distinct chemical entity at the connection between both blocks. With a view towards redox‐sensitive block copolypept(o)ides, a cystamine‐based initiator was used to synthesize polysarcosine macroinitiators with degrees of polymerization ( X n ) between 100 and 200 displaying monomodal molecular weight distributions and dispersities ( Đ ) around 1.1 as determined by size exclusion chromatography. Block copolypept(o)ides with a poly( γ ‐ t ‐butyloxycarbonyl‐l ‐glutamate) (PGlu(O t Bu)) block ( Xn = 25 or 50) were synthesized by controlled N ‐carboxyanhydride polymerization. Resulting block copolymers possess monomodal molecular weight distributions, dispersities around 1.2 and were applied to degradation studies. While block copolypept(o)ides are stable at 10 × 10 −6 m, they degrade over time at GSH concentrations of 10 × 10 −3 and 100 × 10 −3 m . Furthermore, these disulfide‐containing block copolymers form PeptoMicelles, which degrade at intracellular GSH concentrations while remaining stable at extracellular GSH levels. Abstract : The synthesis of amphiphilic block copolypept(o)ides based on bifunctional initiators is described, which allows the incorporation of stimuli‐responsive chemical entities, e.g., disulfides, at the interphase between both blocks. The stimuli‐responsive block copolymers form PeptoMicelles ( R h = 40 nm) in aqueous solution, which disassemble in the presence of glutathione.